PERANAN ETIKA DALAM PEMBELAJARAN DAN PENELITIAN BIOLOGI - Novatul Labibah; Abdul Rasyid Fakhrun Gani; Irine Niandari; Andi Basliahwanti Murti (Bioilmi: Jurnal Pendidikan, 2021)
This study aims to analyze the role of basic ethical principles and codes of ethics in biological research using human and animal subjects, so that academics are expected to understand and apply ethics in their research through biology learning. This study uses qualitative methods through the stages of data collection, data reduction, data presentation, and drawing conclusions. The results show that biological research with human subjects must apply three basic ethical principles including autonomy, generosity, and justice. Three ethical principles that must be applied in biological research with experimental animal subjects are replacement, reduction, and refinement. Thus, the role of ethics in biological research is to regulate researchers in carrying out research regarding what to do, what can and cannot be done through a code of ethics in the form of honesty, integrity, thoroughness, openness, respect for intellectual rights, confidentiality, responsibility for publications, mentoring responsibility, social responsibility, non-discrimination, competence, and legality. Biological research ethics needs to be taught in biology learning so that academics as prospective researchers can understand and comply with them, so that their findings avoid ethical problems that harm humans, animals or the environment.